Core-stable rings in auctions with independent private values - Omer Biran; Françoise Forges (Center for Economic Studies and ifo Institute (CESifo), 2010)
We propose a semi-cooperative game theoretic approach to check whether a given coalition is stable in a Bayesian game with independent private values. The ex ante expected utilities of coalitions, at an incentive compatible (noncooperative) coalitional equilibrium, describe a (cooperative) partition form game. A coalition is core-stable if the core of a suitable characteristic function, derived from the partition form game, is not empty. As an application, we study collusion in auctions in which the bidders' final utility possibly depends on the winner's identity. We show that such direct externalities offer a possible explanation for cartels' structures (not) observed in practice.
Keywords: C71; C72; D44; 330; auctions; Bayesian game; collusion; core; partition function game; Auktionstheorie; Koalition; Bayes-Statistik; Core; Kartell; Theorie